Chemical profiling of organic contaminants in rural surface waters combining target and non-target LC-HRMS/MS analysis. - Fernández García, Alfonso; Martínez Piernas, Ana Belén; Moreno González, David; Gilbert López, Bienvenida; García Reyes, Juan Francisco (Elsevier, 2024)
The pollution of natural waters by contaminants of emerging concern (CECs) is one of the pressing problems due to their global distribution and potential negative effects on the environment and human health. In rural areas with lower population density and limited industrial development, less contamination is expected. However, the lack of wastewater treatment plants (WWTPs) or their poor removal efficiency can lead to significant input of pollutants. In this context, 11 streams of rural areas in the Guadalquivir River basin, southeast of Spain, were studied over two years to obtain an overview of the origin and distribution of contaminants. A target method using solid-phase extraction and liquid chromatography coupled to high resolution mass spectrometry (LC- HRMS) was developed for the analysis of 316 compounds in surface waters. A total of 78 target analytes were detected, comprising pesticides, pharmaceuticals, personal care products (PCPs), transformation products (TPs), and industrial chemicals. The flame retardant tributyl phosphate (16–3572 ng L 1 followed by caffeine (30–8090 ng L 1 ) and the analgesic tramadol (3–1493 ng L ) was detected in all samples, 1 ). The target approach was combined with a non-target analysis (NTA) strategy to obtain an overall perspective of the chemical profile of unexpected or unknown compounds in the samples. Up to 79 contaminants were tentatively identified, and 12 of them were finally confirmed with standards. Most of the contaminants determined by NTA were pharmaceuticals and their TPs. The results indicated that most of CECs have an urban origin despite traditional agriculture is the main economic activity in this region. Moreover, the absence of WWTPs in small towns is significant, as contamination levels at these sites were comparable to or higher than those in larger populations with sewage treatments.
Keywords: Agua - Contaminación; Aguas superficiales; Espectrometría de masas; Química analítica; Surface water; Emerging contaminants; Target analysis; Non-target screening; High-resolution mass spectrometry